Thyroid disorders, etiology and prevalence - Khattak, Muhammad Muzaffar Ali Khan; Khan, Alam (Ansi Network for Scientiific Information, 2002)
The major disorders (problems) of thyroid gland are hyperthyroidism and hypothyroidism, which have been reported in over 110 countries of the world with 1.6 billion people at risk and need some form of iodine supplementation. Usually hyperthyroidism is termed as thyrotoxicosis, but all hyperthyroidism may not represent thyrotoxicosis. Hyperthyroidism and hypothyroidism are due to over and under secretion of thyroid hormones. The most common causes of hyperthyroidism are diffused hyperplasia of the thyroid associated with Graves` disease, the ingestion of excess exogenous thyroid hormones, hyper functional multi nodular goiter and hyper function adenoma of thyroid. Less common causes of hyperthyroidism included certain forms of thyroiditis, thyroid stimulating hormone (TSH) secreting pituitary adenoma and the secretion of excessive amount of thyroid hormones by ectopic thyroid arising in ovarian tetramas. Hypothyroidism usually develops from iodine deficiency. However, in rare cases, it can also be a developed from chronic lymphocytic the thyroiditis, also known as Hashimoto`s disease and from decreased TSH level. Iodine plays an important role in hyperthyroidism and hypothyroidism as iodine is an integral part of thyroid hormones. Availability of iodine to thyroid gland is mainly from foods and water and if these sources are deficient in iodine, then problems like hypothyroidism, cretinism and other iodine deficiency disorders can develop. Similarly, excessive iodine intake in the form of iodized oil, bread and salt can produce hyperthyroidism like iodine induced thyrotoxicosis. The prevalence of hyperthyroidism/ thyrotoxicosis and hypothyroidism vary in different countries. In Pakistan, the prevalence of hyperthyroidism and sub clinical hyperthyroidism was 5.1 and 5.8%, respectively. Similarly, the prevalence of hypothyroidism and sub clinical hypothyroidism was 4.1 and 5.4%, respectively. Prevalence of hyperthyroidism and sub clinical hyperthyroidism was higher in females than males. Similarly, the prevalence of hypothyroidism and sub clinical hypothyroidism was higher in females than males.